Systematic Review and Meta-Analysis of Thermal Stress Assessment in Poultry Using Infrared Thermography in Specific Body Areas - Roberto Carlos Hernández-Sánchez; Francisco Ernesto Martínez-Castañeda; Daniel Alonso Domínguez-Olvera; Maria Elena Trujillo-Ortega; Víctor Manuel Díaz-Sánchez; Ezequiel Sánchez-Ramírez; Elizabeth Posadas-Hernández; Itzayana Mejía-Flores; Elein Hernandez (Animals)
Thermal stress is a health and welfare concern in the poultry industry. Poultry have specific thermoregulation strategies for heat stress (i.e., vasodilatation) or cold stress (i.e., vasoconstriction). Infrared thermal (IRT) analysis is a non-invasive temperature assessment technology with significant benefits compared to conventional temperature measurements, which are invasive and time-consuming. However, a wide range of IRT methodologies and equipment are used for temperature assessment in poultry. The aim of this study was to perform a systematic review and meta-analysis of IRT applications in poultry undergoing thermal stress. The bibliographic search yielded 17 records for qualitative synthesis and 10 for quantitative analysis. The results showed IRT is more commonly studied during heat stress than cold stress, and more research is being conducted on laying hens than other poultry species. Also, four body areas (parts of the head, body, face, and leg) were identified as common areas of interest for body surface temperature measurement. There is a clear thermoregulation response to thermal stress in poultry, with marked differences between featherless and feather-covered areas. IRT in poultry undergoing thermal stress has a good diagnostic value and represents an important welfare assessment tool for future research, particularly when combined with other welfare assessment methods.